The Role and Mechanism of the Vascular Endothelial Niche in Diseases: A Review - Lei, Zhiqiang; Hu, Xiang; Wu, Yaoqi; Fu, Longsheng; Lai, Songqing; Lin, Jing; Li, Xiaobing; Lv, Yanni (Frontiers in Physiology, 2022)
Vascular endothelial cells, forming the inner wall of the blood vessels, participate in the body’s pathological and physiological processes of immunity, tumors, and infection. In response to an external stimulus or internal pathological changes, vascular endothelial cells can reshape their microenvironment, forming a “niche”. Current research on the vascular endothelial niche is a rapidly growing field in vascular biology. Endothelial niches not only respond to stimulation by external information but are also decisive factors that act on neighboring tissues and circulating cells. Intervention through the vascular niche is meaningful for improving the treatment of several diseases. This review aimed to summarize reported diseases affected by endothelial niches and signal molecular alterations or release within endothelial niches. We look forward to contributing knowledge to increase the understanding the signaling and mechanisms of the vascular endothelial niche in multiple diseases.